EFFICIENCY ANALYSIS OF HOTELS LISTED IN THE INDONESIAN STOCK EXCHANGE MARKET - Bire, Rio Benedicto (Jurusan Pariwisata Politeknik Negeri Kupang, 2020)
This paper aims to assess managerial efficiency of the hotels listed in the Indonesian Stock Exchange (IDX) market by applying a Data Envelopment Analysis (DEA) approach. An input oriented DEA assuming both CRS and VRS was employed utilizing data recorded in the companies’ annual reports of year 2017 which encompassed that of revenue, costs and manpower. Research results alluded to identification of both efficient and inefficient hotels, as well as classification for inefficient units, and recognition of peer and peer groups each inefficient hotel can refer to as to project for improvements. Moreover, DEA results provided numerical figures for input reduction each inefficient unit may endeavor. DEA efficiency scores under CRS were proven to be robust, while those under VRS pointed to low discriminatory power. Overall, the application of DEA proved to be a simple yet highly applicable tool for hotel managers to assess performances in regards to managerial efficiency.